Information Literacy Needs in Remote Areas (Case Study on The Island of Aceh) - Cut Afrina (Cyber Media Indonesia, 2021)
The purpose of this research is to know the needs of information literacy in remote areas of Aceh Island. The method in this study is a qualitative research method with a direct approach to the source of research informant namely Pulo Aceh community, long time this research was conducted for four months in Pulo Aceh. The result of this research is that the people of Pulo Aceh should get the same rights in fulfilling the needs of information, they also have the same needs of information literacy as other communities. Therefore, libraries need to pay attention to areas that are left behind in the dissemination of information. The library as an information center should have an effort to reach isolated areas such as Pulo Aceh. Libraries must provide service information regardless of ethnic, racial, geographic location, and other backgrounds. The role of the library in fulfilling the information needs to Pulo Aceh community is more noted and prioritized as an isolated area. With the fulfillment of information needs, they are able to develop competitive with other communities to improve information literacy, but more advanced technological development in order to provide comprehensive information services to remote areas. So they can get information quickly, and relevant and adapted to the needs of the community Pulo Aceh.